AEROGEOFÍSICA DA ÁREA DE SAMAMBAIA NO PROJETO DE ÁGUA SUBTERRÂNEA NO NORDESTE DO BRASIL, CONVÊNIO BRASIL-CANADÁ - Oliveira, Roberto Gusmão de; Monteiro, Alexandre César; Galvão, Manuel Júlio da Trindade Gomes (Águas Subterrâneas, 2001)
Resumo não disponível.